Analisis Bilangan Richardson (Ri) untuk Stabilitas Atmosfer Iklim Mikro pada Maret 2021 di Konawe Selatan - WD, Hendri Satria; Qothrunada, Dewi Tamara; Mondong, Jefri Abednego (Proceedings Series on Physical & Formal Sciences, 2021)
A microclimate is a complex of environmental variables that affect plants, including temperature, radiation, humidity, and wind. One of the additional atmospheric parameters that can be relevant in microclimate studies is the condition of atmospheric stability. The Richardson number derived from the temperature gradient and wind speed can determine the inversion interval in the atmosphere. The research was conducted at the Konawe Selatan Climatology Station to describe the condition of atmospheric stability and the convection process by calculating dynamic stability based on wind and temperature data at the level of 2 meters, 4 meters, and 7 meters in March 2021 from automatic tools. Based on observations in Condition 1, the atmosphere was seen in the morning dominated by neutral conditions, unstable in the afternoon, and stable in the afternoon. In condition 2 the atmosphere on a not rainy day and a rainy day in the morning was dominated by neutral conditions, free convection during the day, and forced convection at night. Free convection illustrated that the wind in the observation area was still dominated by monsoons and was still entering the rainy season. Also, forced convection illustrated that there was orographic rain; this was supported by the topography of the observation area, which was close to the hills and the Boroboro Mountains.